Practical troubleshooting of electrical equipment and control circuits - Brown, Mark. (Newnes, 2005)
There is a large gap between what you learn in college and the practical knowhow demanded in the working environment, running and maintaining electrical equipment and control circuits. Practical Troubleshooting Of Electrical Equipment and Control Circuits focuses on the hands-on knowledge and rules-of-thumb that will help engineers and employers by increasing knowledge and skills, leading to improved equipment productivity and reduced maintenance costs. This book will help engineers and technicians to identify, prevent and fix common electrical equipment and control circuits. The emphasis is on practical issues that go beyond typical electrical principles, providing a tool-kit of skills in solving electrical problems, ranging from control circuits to motors and variable speed drives. The examples in the book are designed to be applicable to any facility. 1. Discover the practical knowhow and rules-of-thumb they don't teach you in the classroom 2. Diagnose electrical problems 'right first time' 3. Reduce downtime.